EDUKASI LITERASI MEDIA BAGI ORANGTUA DALAM PENGGUNAAN GADGET PADA ANAK USIA DINI DI DESA CIBODAS KECAMATAN TANARA KABUPATEN SERANG - Sierfi Rahayu (PARADIGMA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The era of advanced technology and internet access is very easy. But there are both positive and negative impacts resulting from the media. The sophistication of this technology has also been felt in early childhood. The problem that often occurs is the emergence of hoax news and negative content. Service activities aim to provide public understanding of media literacy in the use of gadgets. The method used is education by providing 2 materials, namely media literacy and digital literacy. Participants who participated in this service activity were parents who had early childhood in Cibodas Village, Tanara District, Serang Regency. The result of this activity is that the community feels that they increase their knowledge and understanding of the importance of media literacy for parents in the use of gadgets in children. The recommendation given is that the village government can work with the school on socializing the importance of media literacy for children. So that supervision can be done not only from parents Keywords; Media literacy, gadgets, early childhood